Engineering of the Second‐Harmonic Emission Directionality with III–V Semiconductor Rod Nanoantennas. Issue 9 (20th July 2020) - Saerens, Grégoire; Tang, Iek; Petrov, Mihail I.; Frizyuk, Kristina; Renaut, Claude; Timpu, Flavia; Reig Escalé, Marc; Shtrom, Igor; Bouravleuv, Alexey; Cirlin, George; Grange, Rachel; Timofeeva, Maria
Abstract: The ability to engineer nonlinear optical emission from nanostructures is a key challenge to create efficient and compact components for integrated devices. This paper shows a method to control and manipulate the directionality of second‐harmonic generation emission by engineering geometry and position of rod nanoantennas. Single and dimer nanoantennas are fabricated by slicing III–V semiconductor nanowires with focused ion beam milling. The nonlinear optical response of nanoantennas is tailored by adjusting their length and position to achieve a targeted phase difference. The studied GaAs nanoantennas have a wurtzite structure that allows to achieve preferable directions for the second‐harmonic emission compared to a typical bulk zinc blende structure from top‐down fabricated nanostructures. Wurtzite nanoantennas provide a pure electric dipole response at the second‐harmonic wavelength, which together with pi‐phase control of emitted light is used for designing nonlinear emission patterns. The simulation results show how to redirect the second‐harmonic beam up to 30° and how to tailor the emission profile by adding elements. This method of second‐harmonic generation manipulation and phase array engineering can be applied to different types of nanowires and nanostructures. Nonlinear beam steering with structures from nanowires will foster the creation of compact optical components for integrated circuits. Abstract : A method is demonstrated to control the directionality of the second‐harmonic generation emission by engineering the geometry and position of rod nanoantennas. Single and dimer nanoantennas are fabricated by slicing III–V semiconductor nanowires with focused ion beam milling. The nonlinear optical response of these nanoantennas is tailored by adjusting their length and position to achieve a targeted phase difference.